Analisis Faktor-Faktor Yang Mempengaruhi Pengembalian Kredit Dengan Pendekatan Penelitian Lapangan Analysis Factors Influencing Loan Returnwith A Field Research Approach - Astarini, Dewa Ayu Oki; Murapi, Ikang; Pascayanti, Yusifa; Fahrurrohmi, Hairil (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The development of the MSME business sector is also evenly distributed in various regions in Indonesia, including Mataram City, West Nusa Tenggara Province (NTB). Mataram City is the capital city of NTB Province with a fairly large number of MSME businesses in the culinary and tourism sectors. One of them is Sandubaya District which is the main focus of this study. Mandalika Village which is a business and shopping center area in Mataram City. The type of research used is a quantitative research method with a field research approach to explore deeply and comprehensively related to phenomena in the field, the data used are primary data and secondary data. The data collection technique used is a questionnaire. This study uses multiple linear regression analysis techniques by testing hypotheses, t-tests and f-tests. The results of the study showed that the significance value of the t-test results was obtained, Loan Value had a negative and insignificant effect, Business experience had a positive and significant effect and Length of business had a positive and significant effect on credit returns. Further research recommendations are to add other variables that can influence the variable using other independent variables that can influence the credit return variable, considering that in this study the contribution of the Loan Value variable is not yet significant.